Analysis of the Implementation of Social-Emotional Competence (SEC) Learning in Elementary Schools - Irman Syarif; Puji Yanti Fauziah; Lutfi Wibawa; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2024)
The emphasis on the development of Social-Emotional Competence (SEC) in Elementary Schools has increased during the independence curriculum policy. Still, this emphasis also requires teachers to understand learning strategies and the complex nature of students' social-emotional development. This study explores how schools that implement Social-Emotional Competence (SEC) learning affect students' social-emotional intelligence. This study uses a qualitative descriptive approach. Data were collected through interviews, observations, and documentation to provide conclusions. This study examines the various strategies implemented in this school, including the curriculum, teaching methods, and teacher challenges in implementing SEC Learning. The results of the study indicate that the systematic integration of Social-Emotional Competence (SEC) learning into the Elementary School curriculum significantly positively affects students' social-emotional and academic development.